ROBOTS AS AN ETHNIC MINORITY. OPPRESSION, DEHUMANIZATION AND EXCLUSION IN THE LIGHT OF SCIENCE FICTION LITERATURE - Tassanyi, Pavlína (Bohemica Olomucensia, 2021)
The initial proposal of this work is the classification of humanoid robots as members of a literary ethnic group. Utilising methodological approach of imagology, orientalism and sociology. This thesis deals with mechanism of oppression and social exclusion of robot characters in selected sci-fi work. Exploration of several examples proves that robots are discriminated as ethnic minorities as soon as they demand social equality.
Keywords: robot; science fiction; stereotype; ethnic group; social exclusion; dehumanization